Measurement of the normal mandible in neonates in east China - Jiang, Shupei; Han, Tao; Shen, Weimin (Frontiers in Pediatrics, 2023)
Objective We aimed to measure the related indicators of the neonatal mandible in East China. This provides basic data for the study of the mandible position and morphology of normal newborns and can also provide data support for the diagnosis, evaluation, and treatment of the Pierre Robin sequence. Methods First, we collected the CT data of normal neonates at the Nanjing Children's Hospital Affiliated with Nanjing Medical University between January 2013 and January 2019. The data included the maxilla and mandible, and neonates had no craniomaxillofacial-related malformation. We exported the data in DICOM format. In the second step, we imported the data into MIMICS 21.0 to reconstruct the data into a 3D model, and then we used the model to measure the different measurement items. Specific measurement items were as follows: ① Measurement of the angle α: We imported the CT data of the neonate into the software and reconstructed a 3D model. We observed the 3D model to find the left and right gonions (LGo and RGo) and the Menton (Me) and used the angle measurement tool of the software to appoint Me as the apex, and we connected the points LGo, Me, and RGo as angle α. ② Measurement of the distance between the left and right gonions: The distance measurement tool of the software was used to measure the distance between the bilateral gonions as a. ③ Measurement of the distance from the Me to the line between LGo and RGo: The LGo and RGo were connected as a line on the 3D model, then the distance between Me and the line was measured as b. ④ Measurement of the distance between the upper and lower jaw: The median sagittal view was found and the distance c between the foremost point of the upper jaw and the foremost point of the lower jaw was measured. We imported the measurement results into the SPSS software for statistical analysis. Results Specific measurement results: ① Angle α: 86.34 ± 8.58°. ② Distance a: 63.63 ± 6.83 mm. ③ Distance b: 31.99 ± 3.70 mm. ④ Distance c: 2.28 ± 1.04 mm. Among all the above indicators, there was no statistical difference between gender. Conclusions In this study, 132 neonates were initially screened, of which 117 met the inclusion criteria and were finally included. There were 69 male and 48 female neonates. The indicators α, a, b, and c showed no statistical differences between male and female neonates; therefore, we combined the results to obtain the normal reference value: angle α: 86.34 ± 8.58°; distance a: 63.63 ± 6.83 mm; distance b: 31.99 ± 3.70 mm; distance c: 2.28 ± 1.04 mm.